2017
DOI: 10.1002/jocb.181
|View full text |Cite
|
Sign up to set email alerts
|

Teacher's Encouragement on Creativity, Intrinsic Motivation, and Creativity: The Mediating Role of Creative Process Engagement

Abstract: Drawing on Dewey's pragmatic perspective on talent cultivation and previous research on promoting employee creativity in industry, this study investigates student creativity performance in relation to teacher's encouragement, intrinsic motivation, and creative process engagement. Based on survey data collected from 140 vocational high school students who participated in a nation‐wide contest in Taiwan, path analyses were performed using structure equation modeling techniques. The results indicate that both tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 66 publications
2
7
1
Order By: Relevance
“…In this way, online learning has a positive effect on students learning motivations. By the findings of this research, it has also been confirmed that there is a very closed connection between the intrinsic and extrinsic motivations of the students, which is in line with the theories provided (Gonzalez-DeHass, Willems, & Holbein, 2005;Yuan, Wu, Hu, & Lin, 2019).…”
supporting
confidence: 84%
See 3 more Smart Citations
“…In this way, online learning has a positive effect on students learning motivations. By the findings of this research, it has also been confirmed that there is a very closed connection between the intrinsic and extrinsic motivations of the students, which is in line with the theories provided (Gonzalez-DeHass, Willems, & Holbein, 2005;Yuan, Wu, Hu, & Lin, 2019).…”
supporting
confidence: 84%
“…This study explores the process of integrating Google Classroom in teaching and learning English which might bring positive impacts on increasing students English learning motivationboth intrinsic and extrinsic, later on might improve their academic performance. This is different from other studies (Daskalovska et al, 2012;Gonzalez-DeHass et al, 2005;Koca, 2016;Yuan et al, 2019), which mainly looking at one motivation only without integrating it with technology as their focus.…”
Section: Integrating Technology In Learning Motivationcontrasting
confidence: 69%
See 2 more Smart Citations
“…), since the relationship between creativity and cognitive skills has a variable structure (Kim et al, 2010). The indirect but meaningful motivational effect of the teacher on the student (Yuan, Wu, Hu, and Lin, 2019) also highlighted itself in the results of the study. The Turkish Listening Span Test was carried out in order to measure executive functions in memory (Pickering and Gathercole, 2001) and since the relationship of this concept with creativity is varying (Benedek et al, 2014;Beaty et al, 2014), it was concluded that the findings of the listening span test were partially related to creativity scores.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 56%